JC Virus (JCV) Genotypes in Brain Tissue from Patients with Progressive Multifocal Leukoencephalopathy (PML) and in Urine from Controls without PML: Increased Frequency of JCV Type 2 in PML - Agostini, Hansjürgen T.; Ryschkewitsch, Caroline F.; Mory, Rachel; Singer, Elyse J.; Stoner, Gerald L. (The Journal of infectious diseases, 1997)
Progressive multifocal leukoencephalopathy (PML) is caused by the human polyomavirus JC (JCV), and there are at least 4 different genotypes of JCV in the United States. Type 1 strains are of European origin, whereas type 2 and 3 strains are of Asian and African origin, respectively. JCV type 4 strains are derived from a type 1/3 recombinant. In this study, the genotype distribution of JCV strains found in brain tissue or cerebrospinal fluid of 50 PML patients was compared with JCV genotypes excreted in the urine of 103 control subjects. Type determination was based on the polymerase chain reaction-amplified partial sequence of the VP1 coding gene and the noncoding region left of ori. Brain tissues from patients with PML were infected with a significantly higher proportion of JCV type 2 strains than were urine samples from the control group (P = .004). This evidence indicates a biologic difference between JCV genotypes and suggests a difference in their potential to cause PML.